Identifikasi Rhizoctonia Mikoriza dan Fusarium pada Anggrek Ascocentrum Miniatum - Raden Soelistijono Dwi Susilo Utami Achmadi Priyatmojo (Biota : Jurnal Ilmiah Ilmu-Ilmu Hayati, 2017)
Ascocentrum miniatum (kebutan orchids) is an orchid species in Indonesia is growing in Java. This orchid is rare (Appendix 2) and difficult to be cultivated. One of the obstacles faced in orchid cultivation A.miniatum because they are prone to fungal pathogens. Of the many fungal pathogens that infect, at most dominating is the fungus Fusarium sp.The aim of the research is to identify the mycorrhizal Rhizoctonia contained in A.miniatum orchids that are resistant to the fungus Fusarium sp. This study is the first stage of the three stages of research for 3 years and performed at the Laboratory of Plant Diseases, Faculty of Agriculture UTP using methods that refers to the research conducted by Bayman dkk. (Otero, 2002) and Barnett & Hunter (1972). Each observation was repeated 5 with each replication contained 5 plants. Results showed that characterization of isolates of Rhizoctonia root mycorrhizal A. miniatum derived from Tawangmangu, Bandungan, Kaliurang, Sleman were not morphologically distinct. Equation characters are in colony color, length and number of the cell nucleus, while the characters are in wide differences in the cells and grouped in Tulasnella. Isolation of Fusarium showed macroconidia formation and pathogenicity tests are positive, and the extent of the disease is highest in the 5th month after the inoculation.